The Impact of Debt Financing on Entry and Exit in a Duopoly - Lambrecht, Bart M. (Review of Financial Studies, 2001)
Journal Article The Impact of Debt Financing on Entry and Exit in a Duopoly Get access Bart M. Lambrecht Bart M. Lambrecht University of Cambridge Address correspondence to Bart Lambrecht, Judge Institute of Management Studies, Cambridge CB2 1AG, UK, or e-mail: b.lambrecht@jims.cam.ac.uk. Search for other works by this author on: Oxford Academic Google Scholar The Review of Financial Studies, Volume 14, Issue 3, 1 July 2001, Pages 765–804, https://doi.org/10.1093/rfs/14.3.765 Published: 22 June 2015